Experiences of poverty and exclusion among older adults in a Colla community in northern Chile (Polis (Santiago), 2023)
This scientific article, from a qualitative interpretative methodology, analyzes the experiences of poverty and exclusion in a group of older adults of a Colla community located in the foothills of northern Chile. The comprehensive experiential model establishes that poverty and social exclusion are historical-cultural and transgenerational phenomena, marked from their childhoods, where the postponement, marginalization, discrimination and lack of opportunities in general, establish the path of an indigenous community that, supported by their ancestral practices, marked by values such as solidarity and the sense of community, currently resists the postponement and exclusion of the State, the modern latifundia and the transnational mining companies, which have dispossessed them of their lands and polluted their waters.
Keywords: Poverty; exclusion; Colla community; experiences